To the Question of the Computer Wars History - Alexander A. Galushkin (Èkonomika, Pedagogika i Pravo, 2015)
In the present article author investigates the concept of "cyberwar", history and nature of computer wars studies. Author analyzes opinions of jurists and experts in the field, compares some views on the history of cyberwars. In the conclusion author notes that the solution of the problems connected in the cyberconflicts is impossible without creation of the branch "information law" and its dynamic development, expeditious introduction of timely precepts of law.